A narrow‐band circularly polarized leaky‐wave antenna with open stopband suppressed. Issue 7 (28th April 2021) - Xu, Shen‐Da; Guan, Dong‐Fang; Liu, Li; Zhang, Qingfeng; Xu, Hantao; Yong, Shao‐Wei
Abstract: In this paper, a narrow‐band circularly polarized (CP) microstrip leaky‐wave antenna (LWA) with open stopband suppressed is proposed. Coupled meandered slow‐wave lines are adopted to realize narrow‐band beam scanning. The asymmetric elements are employed as radiators to realize CP and zero‐crossing scanning. We modulated the antenna by loading the ground inductance and asymmetric capacitors on the meandered slow‐wave transmission line. The antenna consists of ten asymmetrical structural elements connected by coupling, the antenna size of L × W is 170 mm × 25 mm. In the operating band of 8.1 to 8.5 GHz, the measured scanning angel of the fabricated antenna is from −31°to +6°. The antenna axial ratios (ARs) are all below 3 dB at the corresponding beam directions. The gain is above 9.1 dBi and the relative bandwidth is only 4.8%. In the operating band, the radiation efficiency is above 60%. It has potential applications in radar detection and wireless communication systems for its simple and low‐profile structure with CP, beam‐scanning, and narrow‐band performance.